Depth-integrated modelling on onshore and offshore sandbar migration: Revision of fall velocity. (February 2017) - Kim, Dae-Hong; Sanchez-Arcilla, Agustin; Caceres, Ivan
Highlights: The fall velocity considering vertical flow can affect sediment suspension and morphology evolution in DI modelling. Suspended load is the main contributor to the morphological change in terms of quantity and quality. On and offshore sandbar migration modelling and analysis on the morphological processes are proposed. Abstract: This paper presents the results of morphodynamic modelling and analysis of onshore and offshore sandbar migration based on a depth-integrated approach. The coastal flow was modeled using the Boussinesq equation and the morphological evolution was modeled using the suspended sediment transport equation and bed load formulae based on the instantaneous velocity and acceleration. The proposed model was applied to the accretive and erosive conditions and the model reproduced the onshore and offshore sandbar migration and the formation of a berm around the shoreline reasonably. An analysis of the computed results revealed the following. (i) The vertical flow velocity can affect the suspension time of the sediments considerably and the bottom evolution. (ii) The suspended load is the main contributor to the morphological changes in terms of the quantity and quality, regardless of the accretive or erosive conditions. (iii) Regardless of accretive or erosive conditions, in terms of the time-average, the instantaneous flow velocity and acceleration-based bed load models always yielded an offshore and onshore direction sediment flux, respectively, except in the swash zone. On the other hand, the suspended sediment flux calculated by the advection-diffusion equation results in the sediment transport in either direction depending on the flow field.